Penerapan Strategi E-Crm Pada Usaha Banana Chips By Risa - Afnida, Riska Fadila; Anggraeni, Dewi; Apridonal M, Yori (J-Com (Journal of Computer), 2025)
Abstract: In today's digital era, small businesses like Banana Chips By Risa face significant challenges in enhancing relationships and services to customers. This research identifies various issues related to technology adoption, including the lack of an online purchasing system, minimal product information, and limited flavor variations. In an increasingly competitive context, the application of information technology becomes crucial to meet the ever-evolving customer expectations. This study aims to design an E-CRM system that can support more effective customer relationship management. E-CRM is a technology-based tool that collects and stores customer data, enhances communication, personalizes services, and analyzes data for better decision-making. Additionally, this system integrates a digital loyalty program expected to increase customer engagement. Several questions arise from the issues faced, including: how to effectively implement an online purchasing system, steps to improve product information, and how to develop new flavor variations that align with customer preferences. The research results indicate that the implementation of E-CRM not only enhances operational efficiency but also strengthens long-term relationships between the business and customers, supporting success in a business environment increasingly influenced by technology. Keywords: e-crm; digital technology; customer loyalty; product Information. Abstrak: Di era digital saat ini, usaha kecil seperti Banana Chips By Risa menghadapi tantangan signifikan dalam meningkatkan hubungan dan pelayanan kepada pelanggan. Penelitian ini mengidentifikasi berbagai masalah terkait adopsi teknologi, termasuk kurangnya sistem pembelian daring, minimnya informasi produk, dan keterbatasan varian rasa. Dalam konteks persaingan yang semakin ketat, penerapan teknologi informasi menjadi krusial untuk memenuhi harapan pelanggan yang terus berkembang. Penelitian ini bertujuan untuk merancang sistem E-CRM yang dapat mendukung pengelolaan hubungan pelanggan secara lebih efektif. E-CRM adalah alat berbasis teknologi yang mengumpulkan dan menyimpan data pelanggan, meningkatkan komunikasi, mempersonalisasi layanan, serta menganalisis data untuk pengambilan keputusan yang lebih tepat. Selain itu, sistem ini juga mengintegrasikan program loyalitas berbasis digital yang diharapkan dapat meningkatkan keterikatan pelanggan. Beberapa pertanyaan yang muncul dari masalah yang dihadapi termasuk: bagaimana cara mengimplementasikan sistem pembelian daring yang efektif, langkah-langkah untuk meningkatkan informasi produk, serta cara mengembangkan varian rasa baru yang sesuai dengan preferensi pelanggan. Hasil penelitian menunjukkan bahwa penerapan E-CRM tidak hanya meningkatkan efisiensi operasional, tetapi juga memperkuat hubungan jangka panjang antara usaha dan pelanggan, mendukung keberhasilan dalam lingkungan bisnis yang semakin dipengaruhi oleh teknologi. Kata kunci: e-crm; teknologi digital; loyalitas pelanggan; informasi produk